A bibliometric analysis of abdominal aortic aneurysm (2014–2024) - Liu, Shao-Jia; Yang, Xin-Qing; Lu, Hong-Qiao; Zhang, Kun-Chi; Tang, Yong-Jiang; Xu, Yu (Frontiers in Cardiovascular Medicine, 2024)
BackgroundAbdominal aortic aneurysm (AAA) is a localized bulge of the abdominal aorta, which mainly manifests as a pulsatile mass in the abdomen. Once an abdominal aortic aneurysm ruptures, the patient's life is seriously endangered. Surgery is the preferred treatment for abdominal aortic aneurysm. At present, there has been no comprehensive review of the current status of abdominal aortic aneurysm research. Therefore, this study aimed to identify global trends in abdominal aortic aneurysm research over the last 10 years through bibliometric analysis and to inform clinical practice, research funding allocation, and decision-making.MethodsWe downloaded research articles and reviews on abdominal aortic aneurysm from 1 January 2014, to 1 March 2024, from the Web of Science core collection. CiteSpace (version 6.2.1), RStudio and VOSviewer (version 1.6.18) were used for visual analysis of regional distribution, institutions, authors, keywords and other information.ResultsThe number of documents on abdominal aortic aneurysm research increased continuously and has stabilized in recent years. A total of 9,905 publications from 67 countries were published from 1 January 2014, to 1 March 2024. A total of 2,142 (29.52%) studies were from the United States, 1,293 (13.05%) were from China, and 919 (9.28%) were from the United Kingdom. A total of 205 studies were conducted at Stanford University, 172 were conducted at Harvard Medical School, and 165 were conducted at the Mayo Clinic. The top three coauthorship authors were Schermerhorn, Marc L (114); Golledge, Jonathan (102); and De Vries, Jean Paul P.M. (74). The most cocited reference was Chaikof EL, 2018, J Vasc Surg, v67, p. 2; the most cocited journal was the Journal of Vascular Surgery; and the most cocited author was Lederle, FA. “Abdominal aortic aneurysm” was the most frequently used author keyword (2,492). Twenty-five references with strong citation bursts were identified by “CiteSpace”. “Artificial intelligence”, “clinical outcomes” and “bridging stent” were the primary keywords of emerging research hotspots.ConclusionThis is the first bibliometric study to comprehensively summarize the research trends in abdominal aortic aneurysm research. This information can help us to identify the current research hotspots and directions. This study will provide extensive help for future research.